FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI BELAJAR SISWA DI ERA PANDEMI COVID-19 - Dyah Lukita Kusumaningrini; Niko Sudibjo (Akademika, 2021)
The pandemic that is being experienced by all countries, including Indonesia, has made learning activities undergo changes. Learning, which was initially carried out face-to-face, must turn into distance learning. This change has an impact on student motivation. Therefore, this study aims to examine three variables that are considered to have an influence on student learning motivation which are the role of parents while accompanying student learning, teacher creativity in designing and managing learning, and also student interest in learning. This research was conducted with a quantitative approach with the PLS-SEM method on 34 students of grade III SD. The results obtained are the role of parents, teacher’s creativity, and interest in learning each have a positive effect on student’s learning motivation. The role of parents is the most influential variable.